The effectiveness of telerehabilitation-based structured exercise therapy for chronic nonspecific neck pain: a randomized controlled trial - Özel, Merve; Kaya Ciddi, Pınar (My University, 2024)
Introduction: The aim of this research was to investigate the effects of telerehabilitation-based remote supervised or unsupervised structured exercise therapy on pain, disability, and quality of life related to chronic nonspecific neck pain. Method: The study was designed as a single-blinded randomized controlled trial. Sixty-six eligible chronic nonspecific neck pain patients were randomized across three groups: remote supervised group (RSG, n = 22), unsupervised group (UG, n = 22), and waitlist control group (CG, n = 22). Progressive structured exercise therapy program was delivered weekly to patients in remote supervised group and unsupervised group to perform four days a week for four weeks. Remote supervised group was supervised by videoconference and text message. Pain, disability, and quality of life of participants were assessed at baseline, week 2, and post-therapy. Results: Post-therapy pain and disability total change scores were ?3.64 (95% CI ?4.85 to ?2.42) and ?7.27 (95% CI ?11.05 to ?3.50) for remote supervised group compared with a change of ?2.44 (95% CI ?3.46 to ?1.43) and ?5.77 (95% CI ?8.54 to ?3.01) for unsupervised group, respectively. Post-therapy, quality of life improvements were greater for remote supervised group than unsupervised group overall (general health; remote supervised group: 19.01 (95% CI 6.86 to 31.16), unsupervised group: 12.50 (95% CI 4.79 to 20.21), and physical health; remote supervised group: 18.35 (95% CI 10.35 to 26.35), unsupervised group: 7.31 (95% CI 0.01 to 14.60)). Significant improvements in psychological health and environment-telerehabilitation for remote supervised group were not seen for unsupervised group and outcomes differences did not reach significance for control group (p > 0.05) post-therapy, except environment-telerehabilitation. Discussion: Structured exercise therapy can improve chronic nonspecific neck pain outcomes when remotely supervised or unsupervised. Structured exercise therapy content and frequent communication are important for remote chronic nonspecific neck pain management.
Keywords: Chronic Neck Pain; Disability; Effectiveness; Exercise Therapy; Randomized Controlled Trial; Telehealth; Telerehabilitation